2014
DOI: 10.5704/moj.1407.010
|View full text |Cite
|
Sign up to set email alerts
|

Cannulated Screw Fixation For Femoral neck Fractures : A 5-year experience In A Single Institution

Abstract: Cannulated screw fixation is a widely accepted surgical method for management of fractures of the neck of femur especially in patients with poor premorbid conditions, minimally displaced fractures and those from a younger age group. A five year retrospective study was carried out in 53 consecutive patients between 2006 to 2010 to determine the pattern of injuries, management, outcomes and the associated predictive factors.All the patients underwent cannulated screw fixation, with 37 (69.8%) having had surgery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Data on age were available for the meta-analysis from 4 studies [16, 17, 19, 28], and nonsignificant heterogeneity was presented among the studies ( I 2 = 17%, P = 0.31). Therefore, the fixed effect model was applied.…”
Section: Resultsmentioning
confidence: 99%
“…Data on age were available for the meta-analysis from 4 studies [16, 17, 19, 28], and nonsignificant heterogeneity was presented among the studies ( I 2 = 17%, P = 0.31). Therefore, the fixed effect model was applied.…”
Section: Resultsmentioning
confidence: 99%
“…A 17-item survey showed that for the undisplaced fracture near 80% surgeons prefer using OCCS [ 14 ]. In the retrospective study of 59 patients in a single institution, 4/5 of them treated with OCCS showed good results at last [ 15 ]. However, for the more vertical fracture, the rate of failure and complication has risen obviously because of the increase of shear force [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the younger population, primary osteosyntheisis is recommended as it is relatively inexpensive and minimally invasive procedure. Also with adequate reduction, maximal bone contact can be achieved which is sufficient for early immobilization and efficiently promote bone healing 1 7 14) . Specially, when the cannulated screw is used as a fixation method, the use of guide wire can accurately determine the size and the position of the screw thereby providing optimal stability even with minimal invasion to the fracture site 4 11) The operation of femoral neck fracture is usually perfromed with the use of fracture table but in the current series, all operations were performed using conventional operation table.…”
Section: Discussionmentioning
confidence: 99%
“…However, the operation result depends on the experience and proficiency of the operator and the exposure to radiation by the fluoroscopy, risk of fixation failure, nonunion and AVN remains possible complications 1 2 3 4) . When the primary osteosynthesis is attempted in the femoral neck fracture, AVN is reported to occur in 10-45% and nonunion in 10-30% 3 5 6 14 15) . This is consistent with our series as the nonunion occurred in 11% and AVN in 22%.…”
Section: Discussionmentioning
confidence: 99%